Anthroponymy in the worldview of Medieval Turkic Mamluks (Based on the “Kitāb-i maǧmūʿ-i tarǧumān-i turkī wa ʿaǧamī wa muġālī wa fārsī” (XIV century)) - Jubatova Б. (Turkic Studies Journal, 2026)
This article examines historical anthroponymy not merely as a system of linguistic nomination, but as a cultural structure reflecting historical memory, value systems, and social hierarchy. The study focuses on anthroponymic data recorded in a Turkic–Arabic dictionary compiled in medieval Egypt under conditions of Arabic linguistic dominance. Mamluk anthroponymy constitutes an important source for reconstructing the social structure and value system of a polyethnic and multilingual society, as it reveals the complex interaction between Turkic traditions and Arab-Islamic cultural frameworks. The primary source is the fourteenth-century Arabic–Turkic dictionary known as ‘Kitāb-i Majmūʿ-i Tarjumān-i Turkī wa ʿAjamī wa Mughalī wa Fārsī’ (Tarjumān), compiled in Egypt. Its twenty-second section contains personal names of Mamluks, jāriyas, and representatives of other social groups. In total, this section records 84 anthroponyms, of which 64 refer to men and 20 to women. This distribution reflects both the predominance of the military-administrative elite in the source material and the gender asymmetry characteristic of medieval society. Unlike narrative and official sources, the dictionary preserves anthroponyms used in everyday linguistic practice and, through Arabic translations and glosses, enables the reconstruction of their semantic content. The aim of this study is to identify the semantic and functional features of Turkic-Mamluk anthroponyms in the dictionary and to demonstrate the interpretive potential of personal names for reconstructing the worldview of the Turkic Mamluks through an analysis of socio-cultural naming practices. Methodologically, the study adopts an interdisciplinary approach integrating historical onomastics, ethnolinguistics, and linguistic anthropology. Anthroponyms are analyzed through semantic classification and contextual interpretation, with particular attention to military-status markers, zoonymic symbolism, strength-related semantics (e.g., iron, stone, gold), and apotropaic functions. Female anthroponyms are examined in relation to the social category of jāriya/jawārī and are interpreted within the framework of palace institutional structures, where they fulfilled aesthetic and symbolic functions. The scholarly contribution of this study lies in its comprehensive analysis of Turkic anthroponymy in the ‘Tarjumān’ not merely as lexicographic material, but as an integral element of the social and symbolic space of Mamluk society. For the first time, Turkic personal names are interpreted as mechanisms for preserving group identity among the military elite, symbolically legitimizing social status, and transmitting pre-Islamic cultural layers within an Islamic context. Furthermore, female anthroponyms associated with jāriyas are analyzed from a gendered and institutional perspective, revealing the close relationship between naming practices, power structures, and socialization processes. The study also differentiates between personal names, nisbas, and nicknames, situating anthroponyms within their broader historical and cultural context.